Lifestyle factors modified the mediation role of liver fibrosis in the association between occupational physical activity and blood pressure - Zhang, Shangyi; Chen, Zhenlong; Jiang, Xinman; Zhou, Shenglan; Liu, Yanru; Liu, Mingsheng; Dai, Xiayun; Lu, Bifeng; Yi, Guilin; Yin, Wenjun (Frontiers in Public Health, 2024)
The study aimed to estimate the role of liver fibrosis in the association of occupational physical activity (OPA) with blood pressure, which is modified by lifestyle factors.The questionnaire survey and physical examination were finished among 992 construction workers in Wuhan, China. Associations of OPA or lifestyle factor with liver fibrosis indices and blood pressure were assessed using generalized additive models. Mediation analysis was used to evaluate the role of liver fibrosis on the association of OPA and lifestyle factor with blood pressure.Results: Moderate/high OPA group workers had an increased risk of liver fibrosis (OR = 1.69, 95%CI: 1.16 -2.47, P < 0.05), compared with low OPA group workers. Smoking or drinking alcohol was related to liver fibrosis (aspartate aminotransferase to platelet ratio index: odd ratio = 2.22, 95% confidence intervals (CI): 1.07 -4.62 or odd ratio = 2.04, 95%CI: 1.00 -4.15) (P < 0.05). Compared with non-drinkers, drinkers were related to 2.35 mmHg increase in systolic blood pressure (95%CI: 0.09 -4.61), 1.60 mmHg increase in diastolic blood pressure (95%CI: 0.08 -3.13), respectively (P < 0.05). We found a significant pathway "OPA → liver fibrosis → blood pressure elevation", and lifestyle factors played a regulatory role in the pathway.Conclusions: OPA or lifestyle factor were associated with liver fibrosis indices or blood pressure in construction workers. Furthermore, the association between OPA and blood pressure may be partially mediated by liver fibrosis, lifestyle factors strengthen the relationship between OPA and blood pressure and the mediation role of liver fibrosis in the relationship.